Evaluation of feed resources in mixed crop-livestock systems in Sudano-Sahelian zone of Mali in West Africa - Umutoni, Clarisse; Ayantunde, Augustine A.; Sawadogo, G.J. (ScopeMed, 2015)
Livestock are important assets to the rural poor in developing countries but are faced with the major challenge of marked seasonal feed availability. A study was carried out to assess existing and potential feed resources and constraints to livestock production in Southern part of Mali. A feed assessment tool was used to collect necessary data. The assessment included focus group discussions and individual interviews. Results showed that seasonal shortage in feed supply, absence of livestock route and lack of watering points were the major constraints facing livestock production in the study areas. Pastures and green forage were the main feed for animal during the wet season while crop residues, fodder trees and shrubs were the main source of feed in the dry season. Results further showed that almost all types of crop residues were used for livestock feeding compared to other uses. The highest dry matter contents of ruminants’ total diet came from grazing.